On the boundedness of some nonlinear differential equation of second order - Guzmán, Paulo Matias (2015)
In this paper we study the boundedness of the solutions of some nonlinear dofferential equation using as a key tool the Second Lyapunov method, i.e. find sufficient conditions under which the solutions of this equation are bounded. Variuos particular cases and methodological remarks are included at the end of paper.